Hubungan antara Tingkat Pemahaman Piktogram (Label Keamanan Kimia) dan Sikap terhadap Kepatuhan Kesehatan dan Keselamatan Kerja di Laboratorium Kimia Universitas Nusa Cendana - Karolus Tokan, Yohanes; Roga, Anderias Umbu; Muntasir, Muntasir; Ratu, Jacob M; Riwu, Magdarita (Jurnal Biomedika dan Kesehatan, 2024)
Background Students' knowledge of OHS is a basic knowledge that must be possessed by students before and during experiments in chemistry laboratories. Hazard pictograms warn us of the presence of hazardous chemicals. Student compliance with OHS and basic knowledge that students must have before and during experiments in chemistry laboratories. This research was to analyze the relationship between the level of knowledge, skills, and occupational health and safety (OHS) compliance in the Chemistry Laboratory at Nusa Cendana University to minimize risks and prevent occupational accidents in the Laboratory. Methods Observational analytical research with cross-sectional design. The population was students of Chemical Education (FKIP), Chemical Science Students (FST), and Pharmacy Students (FKKH) of Nusa Cendana University. A sample of 75 samples was taken. Data were collected using a questionnaire that was observed during February - March 2024. Measurement of the average value of compliance, attitude, and knowledge between the three study programs using statistical analysis conducted is univariate and bivariate using the chi-square test (p=0.05). Results The attitude variable has a significant effect on compliance. In the skill variable statistical results on SPSS version 25 with Chi-Square analysis, the results obtained a p-value of 0.330 (>0.05) which can be concluded that there is no relationship between OSH compliance in Nusa cendana university students.  The attitude variable has a significant effect on compliance. The positive coefficient value indicates that the influence exerted by attitude on compliance is positive. Statistical results on SPSS version 25 with Chi-Square analysis, the results obtained a p-value of 0.000 (>0.05) which can be concluded that there is a relationship between the level of attitude towards OHS compliance in students.     Conclusions The level of knowledge of students does not have a significant effect on compliance in OHS, while Attitude, has a significant effect on OHS Laboratory OHS.